Dewan Adat Suku Ngalum: Warisan Pengetahuan Tradisional untuk Generasi Milenium di Papua - Davit Mimin; Tenas Kisamlu; Handrianus Koli Belolon (UNES Law Review, 2023)
The preservation of the Ngalum Tribe's culture serves as the key to their identity. This research highlights the lack of understanding among the general public regarding Papua's tribes, revealing the uniqueness of the Ngalum Tribe and identifying obstacles in preserving their educational and traditional knowledge heritage. Employing qualitative research methods, the study focuses on the role of the Ngalum Tribe's Council of Customs in transferring cultural knowledge and sustaining traditional values in the Oksibil District, Pegunungan Bintang Regency. Data collection involved observation, interviews, document studies, and analysis through data triangulation. The results indicate that the development of the Ngalum Tribe's traditional teaching system is less effective, with a lack of creativity among the millennial generation and various challenges such as difficulties in developing cultural tools, high maintenance costs, and insufficient understanding of traditional dances. Improvements entail an innovative approach to the teaching system, active support for millennial creativity, and the exploration of financial solutions. Despite the challenges, the preservation efforts are progressing well.